Para-Trifluoromethyl-methcathinone is an allosteric modulator of the serotonin transporter. (15th December 2019) - Niello, Marco; Cintulova, Daniela; Hellsberg, Eva; Jäntsch, Kathrin; Holy, Marion; Ayatollahi, Leila H.; Cozzi, Nicholas V.; Freissmuth, Michael; Sandtner, Walter; Ecker, Gerhard F.; Mihovilovic, Marko D.; Sitte, Harald H.
Abstract: The transporters for dopamine (DAT) and serotonin (SERT) are important targets in the treatment of psychiatric disorders including major depression, anxiety and attention-deficit hyperactivity disorder. Drugs acting at these transporters can act as inhibitors or as releasers. In addition, it has been recently appreciated that some compounds are less efficacious releasers than amphetamine. Thus, they are classified as partial releasers. Compounds can act on both SERT and DAT or display exquisite selectivity for either SERT or DAT, but the structural basis for selectivity is poorly understood. The trifluoromethyl-substitution of methcathinone in the para -position has been shown to dramatically shift the selectivity of methcathinone (MCAT) towards SERT. Here, we examined MCAT, para -trifluoromethyl-methcathinone (pCF3 MCAT) and other analogues to understand (i) the determinants of selectivity and (ii) the effects of the para -CF3 -substitution of MCAT on the transport cycle. We systematically tested different para -substituted MCATs by biochemical, computational and electrophysiological approaches: addition of the pCF3 group, but not of other substituents with larger van der Waal's volume, lipophilicity or polarity, converted the DAT-selective MCAT into a SERT-selective partial releaser. Electrophysiological and superfusion experiments, together with kinetic modelling, showed that pCF3 MCAT, but not MCAT, trapped a fraction of SERTs in an inactive state by occupying the S2-site. These findings define a new mechanism of action for partial releasers, which is distinct from the other two known binding modes underlying partial release. Our observations highlight the fact that the substrate permeation pathway of monoamine transporters supports multiple binding modes, which can be exploited for drug design. This article is part of the issue entitled 'Special Issue on Neurotransmitter Transporters'. Graphical abstract: Image 1 Highlights: Para -CF3 -substitution of MCAT allows to selectively target SERT over DAT. MCAT and para- CF3 -MCAT are partial releasers of SERT. The partial release evoked by para- CF3 -MCAT involves the allosteric site of SERT. The substrate permeation pathway of SERT affords different binding modes.